Clinical presentation and management of primary ovarian neuroendocrine tumor in multiple endocrine neoplasia type 1. (20th August 2019) - Jhawar, Sakshi; Lakhotia, Rahul; Suzuki, Mari; Welch, James; Agarwal, Sunita K; Sharretts, John; Merino, Maria; Ahlman, Mark; Blau, Jenny E; Simonds, William F; Del Rivero, Jaydira
Abstract : Summary: Multiple endocrine neoplasia type 1 (MEN1) is an autosomal dominant condition characterized by parathyroid, anterior pituitary and enteropancreatic endocrine cell tumors. Neuroendocrine tumors occur in approximately in 5–15% of MEN1 patients. Very few cases of ovarian NETs have been reported in association with clinical MEN1 and without genetic testing confirmation. Thirty-three-year-old woman with MEN1 was found to have right adnexal mass on computed tomography (CT). Attempt at laparoscopic removal was unsuccessful, and mass was removed via a minilaparotomy in piecemeal fashion. Pathology showed ovarian NET arising from a teratoma. Four years later, patient presented with recurrence involving the pelvis and anterior abdominal wall. She was treated with debulking surgery and somatostatin analogs (SSAs). Targeted DNA sequencing analysis on the primary adnexal mass as well as the recurrent abdominal wall tumor confirmed loss of heterozygosity (LOH) at the MEN1 gene locus. This case represents to our knowledge, the first genetically confirmed case of ovarian NET arising by a MEN1 mechanism in a patient with MEN1. Extreme caution should be exercised during surgery as failure to remove an ovarian NET en masse can result in peritoneal seeding and recurrence. For patients with advanced ovarian NETs, systemic therapy options include SSAs, peptide receptor radioligand therapy (PRRT) and novel agents targeting mammalian target of rapamycin (mTOR) and vascular endothelial growth factor (VEGF). Learning points: Ovarian NET can arise from a MEN1 mechanism, and any adnexal mass in a MEN1 patient can be considered as a possible malignant NET. Given the rarity of this disease, limited data are available on prognostication and treatment. Management strategies are extrapolated from evidence available in NETs from primaries of other origins. Care should be exercised to remove ovarian NETs en bloc as failure to do so may result in peritoneal seeding and recurrence. Treatment options for advanced disease include debulking surgery, SSAs, TKIs, mTOR inhibitors, PRRT and chemotherapy.